Gender Differences in Managers' Developmental Job Experiences - Ohlott, Patricia J.; Ruderman, Marian N.; McCauley, Cynthia D. (Academy of Management Journal, 1994)
It has been suggested that one reason so few women have been promoted to senior management positions is that during their careers they experience fewer developmental job opportunities than men. To test this idea, we surveyed male and female managers about developmental components in their current jobs. Results suggest that men experience some greater task-related developmental challenges, but women experience greater developmental challenges stemming from obstacles they face in their jobs.